Prevention and resolution of constitutional conflicts: concept and methods - Irina A. Tretyak (Правоприменение, 2020)
The subject. The article is devoted to different methods of constitutional conflicts resolution, classification of constitutional conflicts, genesis of constitutional conflict diagnostics theory as a system of different measures for constitutional conflicts prevention.The purpose of the article is to confirm or disprove hypothesis that methods of constitutional conflicts resolution and prevention may be classified by different bases.The methodology of the study includes general scientific methods (analysis, synthesis, description) as well as sociological and economic approaches. The main results and scope of their application. The author describes different groups of conflict resolution methods, it’s types and system. The optimal way to resolve the constitutional conflict is systematic application of the following principles: 1) the legality of measures; 2) priority of human and civil rights and freedoms; 3) ultimo ratio (last resort); 4) proportionality of measures; 5) the effectiveness of measures, aimed at resolving the constitutional conflict. Conclusions. Constitutional conflicts are resolved by special legal methods. Depending on the enforceability of such methods for the conflicting parties, such methods can be classified into: - enforcement methods, that are based on the constitutional power of legal enforcement to be applied to one side of the conflict by the other party or by the actor of the constitutional-legal conflict (measures of constitutional enforcement, the mechanism of checks and balances); - cooperative methods, which are understood as mechanisms for resolving constitutional conflicts, enshrined in the norms of constitutional law and based on cooperation, mutual assistance of the parties to the conflict on a parity basis (various forms of coordination, such as negotiations, mediation, conciliation). Methods and mechanisms of conflicts prevention are not the part of methods of resolving constitutional conflicts, since the first methods are applied before the appearance of constitutional and legal conflicts. A constitutional conflict diagnostics as a method of constitutional conflict prevention is based on risk management system and represents a system of legal and organizational measures, aimed at identifying risks of constitutional conflicts and legal monitoring.